SOUNDSCAPE KAWASAN: EVALUASI RUANG BERKELANJUTAN - Syamsiyah, Nur Rahmawati; Dharoko, Atyanto; Utami, Sentagi Sesotya (Jurnal Arsitektur ARCADE, 2019)
Abstract: The density of major cities in Indonesia is the impact of the rapid development of the population. Increasing the population as well as their welfare make the residential and traffic environment in urban areas less healthy. Noisy, and air quality as the main indicators that can be felt to be very disturbing to the human environment. The sound quality perspective is one that is overlooked. Even though the government of the Republic of Indonesia has issued standard noise levels in Kep-48 / MENLH / 11/1996, evaluation and control of reality in the field is still lacking. The soundscape approach that is very concerned about the environment as a resource will be the most effective when applied in urban and regional planning. This paper aims to explore how sound impacts in providing an auditory experience in open space through a soundscape approach with case studies of open space or the court of the Great Mosque of Yogyakarta. This case can be an example of implementing a strategy to create peace of space in the midst of the hustle and bustle of the city. On the other hand soundscaping techniques become the needs of every city to do, and in particular there must be a spatial pattern that unites and adapts to each other between buildings, open spaces, vegetation, water elements and activities, so that the sustainability of a comfortable and calm space will last long. Keywords: space sustainability; noise; auditory experience; soundscapeAbstrak: Kepadatan kota-kota besar di Indonesia merupakan dampak perkembangan penduduk yang begitu cepat meningkat. Peningkatan jumlah penduduk sekaligus kesejahteraan mereka membuat lingkungan pemukiman dan lalu lintas di perkotaan semakin kurang sehat. Bising, dan kualitas udara sebagai indikator utama yang dapat dirasakan sangat mengganggu lingkungan hidup manusia. Perspektif kualitas suara adalah salah satu yang terabaikan. Sekalipun pemerintah Republik Indonesa sudah mengeluarkan baku tingkat kebisingan dalam Kep-48/MENLH/11/1996, namun evaluasi dan kontrol terhadap kenyataan di lapangan masih kurang dilakukan. Pendekatan soundscape yang sangat memperhatikan lingkungan sebagai sumber daya akan menjadi yang paling efektif bila diterapkan dalam perencanaan kota dan kawasan. Tulisan ini bertujuan untuk mengeksplorasi bagaimana dampak suara dalam memberikan pengalaman auditory dalam ruang terbuka melalui pendekatan soundscape dengan studi kasus kawasan ruang terbuka atau pelataran Masjid Agung Yogyakarta. Kasus ini dapat menjadi contoh penerapan strategi menciptakan ketenangan ruang di tengah hiruk pikuk kota. Di sisi lain teknik soundscaping menjadi kebutuhan setiap kota untuk dilakukan, dan secara khusus harus ada pola spasial yang menyatukan dan saling menyesuaikan antara bangunan, ruang terbuka, vegetasi, unsur air dan aktifitas, sehingga keberlanjutan ruang kawasan yang terkondisi nyaman dan tenang akan bisa bertahan lama.Kata Kunci: keberlanjutan ruang; kebisingan; pengalaman auditory; soundscape